Petrogenesis and relationship with REE mineralization of the quartz syenite from Chishan and Longbaoshan alkaline complex, southeastern North China Craton: Insights from zircon U–Pb geochronology, element, and Sr–Nd–Pb–Hf isotope geochemistry - Wei, Pengfei; Li, Dapeng; Song, Zhigang; Liu, Qiang; Geng, Ke; Zhang, Yan; Ding, Chengwu; Cai, Na; Li, Zengsheng; Zhang, Chao; Xie, Wei (Frontiers in Earth Science, 2023)
Mesozoic alkaline complexes associated with the rare earth element (REE) mineralization are developed in southeastern North China Craton (NCC) and they recorded some important information about the lithospheric thinning and destruction of the NCC. Zircon U-Pb dating results reveal that the syenitic rocks from the Chishan and Longbaoshan alkaline complexes were emplaced at ca. 126.2–123.7 Ma. These syenitic rocks have an arc-like affinity with enriched LREEs and LILEs (e.g. Ba and Th) and depleted HFSE (e.g. Nb and Ta). However, they plot within the extensional alkaline-calc-alkaliline field in the lg(CaO/(K2O + Na2O)) versus SiO2 discrimination diagram and plot within the fields of divergent plate & within-plate settings in the NbN versus ThN discrimination diagram, implying an extensional tectonic setting. Thus, we suggest that the syenitic rocks should formed in an extensional tectonic settings related to rollback and retreat of the subducting Paleo-Pacific plate. These syenitic rocks have similar Sr-Nd-Pb-Hf isotope compositions ((87Sr/ 86Sr)i = 0.7062 to 0.7101, εNd(t) = -8.2 to -15.0, εHf(t) = −13.5 to −9.6), which are the same as the enriched subcontinental lithospheric mantle (SCLM) of the NCC. Taking into account not only our new data but also previously published data regarding the evolution of NCC in Mesozoic, we conclude that the syenitic rocks from the Chishan and Longbaoshan complexes are derived from partial melting of the lithospheric mantle triggered by the Paleo-Pacific plate subduction. Moreover, the geochemical and Sr-Nd-Pb isotopic similarity between the Chishan REE ores, Longbaoshan altered rocks and the syenitic rocks implies that they are homologous products of Early Cretaceous, and that the mineralization shows inheritance to the magmatic hydrothermal evolution.